En modell för ordbokskritik - Koukkunen, Kalevi (Nordiske Studier i Leksikografi, 1997)
For this article, the author has studied reviews ofbilingual and monolingual Finnish dictionaries startingfrom 1826 up to the 1990s. The aim has been to find out ifit is possible to distinguish patterns of common and repeated elements in dictioruuy reviews (κ), and whether these elements could be worked into a specific formula. An analysis of the content of the reviews studied shows that the following elements can be considered as regular features of a dictioruuy review: 1) generalities (κ1; historical reasons forpublishing the dictionary, goals ofthe dictionary, layout, guide for users), 2) analys is of the entries ( λ; equivalents, idioms, structure ), 3) lexikographical problems ( λ1), 4) importance ofthe dictionary (α). It is shown that the foregoing elements can be worked into the following formula: κ = κ1 + λ + λ1 + α. When λ1 anda are reduced to λ, we get the following formula: K = K 1 + λ. Results of empirical testing are also provided in this article.